2022
DOI: 10.3389/fimmu.2022.986118
|View full text |Cite
|
Sign up to set email alerts
|

The potential roles of interleukin-25 in infectious diseases

Abstract: Interleukin-25 (IL-25), also known as IL-17E, is a recently identified cytokine of the IL-17 family. Numerous studies illustrated that the expression of IL-25 is regulated by multiple pathogens, including parasitic, viral, and bacterial infections. IL-25 has a dual function in infectious diseases. On the one hand, IL-25 activates type 2 immunity via the relevant cytokines, including IL-4, IL-5, and IL-13, which are associated with the development of pathogenic infection-related allergic diseases. On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 121 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…IL‐25 belongs to the IL‐17 family, also known as IL‐17E, 11 and has been identified as an “alarmin” cytokine that responds to pathogenic infection 12,13 . After infection, IL‐25 is produced rapidly and promotes innate lymphoid cell proliferation 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐25 belongs to the IL‐17 family, also known as IL‐17E, 11 and has been identified as an “alarmin” cytokine that responds to pathogenic infection 12,13 . After infection, IL‐25 is produced rapidly and promotes innate lymphoid cell proliferation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-25 belongs to the IL-17 family, also known as IL-17E, 11 and has been identified as an "alarmin" cytokine that responds to pathogenic infection. 12,13 After infection, IL-25 is produced rapidly and promotes innate lymphoid cell proliferation. 14 A previous study has reported that tuft cell expansion was modulated by IL-25 expression during parasitic and bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that apart from Th2 cells, a rare population of epithelial cells that are recognized as tuft cells is an important source of IL-25 in the intestinal environment [ 21 ]. Tuft cells are a group of rare secretory epithelial cells mainly distributed in the respiratory tract and gastrointestinal tract [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-25 –/– mice infected by Trichuris showed intestinal inflammation associated with increased expression of interferon γ (IFN-γ) and IL-17 [ 65 ]. IL-25 reduces Th1 cytokines such as IL-1, IL-6, and TNF-α produced by most helminth infections [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation